2008
DOI: 10.1152/jn.01282.2007
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold Membrane-Potential Resonances Shape Spike-Train Patterns in the Entorhinal Cortex

Abstract: Many neurons exhibit subthreshold membrane-potential resonances, such that the largest voltage responses occur at preferred stimulation frequencies. Because subthreshold resonances are known to influence the rhythmic activity at the network level, it is vital to understand how they affect spike generation on the single-cell level. We therefore investigated both resonant and nonresonant neurons of rat entorhinal cortex. A minimal resonate-and-fire type model based on measured physiological parameters captures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 54 publications
5
83
1
Order By: Relevance
“…The oldest report that is known to the authors is in the activity of motoneurons in humans (Hagiwara 1949). Subsequent studies have found nonrenewal spiking statistics in retinal cat retinal ganglion cells (Kuffler et al 1957;Rodieck 1967;Levine 1980), cat superior olivary neurons (Goldberg et al 1964;Tsuchitani and Johnson 1985), cat peripheral auditory fibers (Lowen and Teich 1992), cat cochlear nuclear neurons (Goldberg and Greenwood 1966), cat medullary sympathetic neurons (Lewis et al 2001), cat sympathetic efferent fibers (Floyd et al 1982), pigeon vestibular afferents (Correia and Landolt 1977), weakly electric fish electroreceptor neurons (Longtin and Racicot 1997;Chacron et al 2000;Ratnam and Nelson 2000;Chacron et al 2001b;Chacron et al 2005b;Gussin et al 2007), paddlefish electroreceptors (Bahar et al 2001;Neiman and Russell 2001;Neiman and Russell 2004), catfish electroreceptors (Schäfer et al 1995), weakly electric fish electrosensory pyramidal neurons (Doiron et al 2003;Chacron et al 2007), honeybee mushroom body neurons (Farkhooi et al 2009), grasshopper auditory neurons (Schwalger et al 2010), primate spinothalamic neurons (Surmeier et al 1989), rat mesencephalic reticular neurons (Lansky and Radil 1987), primate somatosensory cortical neurons (Yamamoto and Nakahama 1983;Lebedev and Nelson 1996;Nawrot et al 2007), as well as rat entorhinal cortical pyramidal and interneurons (Engel et al 2008). We note that the last five studies challenge the notion that cortical neurons can be described by a renewal process such as the Poisson process and shall return to this point later.…”
Section: Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The oldest report that is known to the authors is in the activity of motoneurons in humans (Hagiwara 1949). Subsequent studies have found nonrenewal spiking statistics in retinal cat retinal ganglion cells (Kuffler et al 1957;Rodieck 1967;Levine 1980), cat superior olivary neurons (Goldberg et al 1964;Tsuchitani and Johnson 1985), cat peripheral auditory fibers (Lowen and Teich 1992), cat cochlear nuclear neurons (Goldberg and Greenwood 1966), cat medullary sympathetic neurons (Lewis et al 2001), cat sympathetic efferent fibers (Floyd et al 1982), pigeon vestibular afferents (Correia and Landolt 1977), weakly electric fish electroreceptor neurons (Longtin and Racicot 1997;Chacron et al 2000;Ratnam and Nelson 2000;Chacron et al 2001b;Chacron et al 2005b;Gussin et al 2007), paddlefish electroreceptors (Bahar et al 2001;Neiman and Russell 2001;Neiman and Russell 2004), catfish electroreceptors (Schäfer et al 1995), weakly electric fish electrosensory pyramidal neurons (Doiron et al 2003;Chacron et al 2007), honeybee mushroom body neurons (Farkhooi et al 2009), grasshopper auditory neurons (Schwalger et al 2010), primate spinothalamic neurons (Surmeier et al 1989), rat mesencephalic reticular neurons (Lansky and Radil 1987), primate somatosensory cortical neurons (Yamamoto and Nakahama 1983;Lebedev and Nelson 1996;Nawrot et al 2007), as well as rat entorhinal cortical pyramidal and interneurons (Engel et al 2008). We note that the last five studies challenge the notion that cortical neurons can be described by a renewal process such as the Poisson process and shall return to this point later.…”
Section: Overviewmentioning
confidence: 99%
“…Several investigators have reported nonrenewal spike train statistics in the form of a negative ISI serial correlation coefficient at lag 1 that is significantly different from zero (Kuffler et al 1957;Goldberg et al 1964;Yamamoto and Nakahama 1983;Tsuchitani and Johnson 1985;Schäfer et al 1995;Chacron et al 2000;Chacron et al 2007;Nawrot et al 2007;Engel et al 2008;Farkhooi et al 2009). As mentioned above, this implies that ISIs that are shorter than average tend to be followed by ISIs that are longer than average and vice versa, thus giving rise to patterning in the spike train.…”
Section: Negative Interspike Interval Correlations At Lagmentioning
confidence: 99%
See 3 more Smart Citations